Immunization Status of Children Under 5 Years in A Tribal Area, Parol, Thane District - Naveen C Khargekar; Vandana C Khargekar; Poonam P Shingade (Medsci Publications, 2015)
Background: Infectious diseases are a major cause of morbidity and mor- tality in children. One of the most cost-effective and easy methods for the healthy well-being of a child is immunization. In India, immunization services are offered free in public health facilities, but despite rapid in- creases, the immunization rate remains low in some areas. Objectives: The objective of the study was to study the socio- demographic profile and immunization status of the children aged less than 5yrs. Materials and Methodology: The present study was carried out in a tribal area of Parol in Thane district. In this descriptive cross sectional study tribal children in the age group of 1-5 years were assess for their immunization status. Results: Completely immunized children were 71.1%, partially immu- nized were 17.8% and 11.1% were not immunized. The most common reason for not immunizing the child was 'fear of side effects' (40%) and for partially immunizing the child was 'visit to native place' or 'other sibling not well' (37.5%). There was significant association between poor immunization status and Muslim religion of the children, poor socio- economic status, home delivery, and not having immunization card. Conclusion: The overall coverage of immunization among the tribal area is good but still it has pockets of poor immunization.